Classification of concentration or focus by signal Electroencephalography (EEG) and addiction Watching K-Dramas Using Algoritma K-Nearest Neighbor - Azhari, Ahmad; Ramadan, Rizky (Association for Scientific Computing Electrical and Engineering (ASCEE), 2019)
K-drama or drakor is currently being enjoyed in Indonesia when the Covid-19 pandemic hits, especially by the fair sex. From the sources obtained, the number of k-dramas or dramas also increased during the covid-19 pandemic from the previous 2.7 hours a day to 4.6 hours a day. The issue raised by the authors in this study is whether the impressions of drakor will later affect the concentration of an individual. Data acquisition was carried out using the NeuroSky Mindwave Mobile 2 tool to retrieve EEG data.Â After the data acquisition is completed, the next process is preprocessing, which is to perform feature extraction using the Fast Furious Transform method to find the average values of the highest and lowest peaks. After the preprocessing is completed go to the classification stage. The classification used is K-Nearest Neighbor with a value of k=9.Â For evaluation using confusion matrix to determine the accuracy value of the built KNN model. This study used 100 respondents who were37 people who were addicted to drakor. A total of 24 people out of the 37 or about 64.87% turned out to have a lack of concentration level when taking concentration tests. This is enough to prove that drama impressions can reduce the concentration or focus of a person, especially women. For the classification process to have an accuracy of 80% and for variable correlation testing, it turns out that independent variables do have a simultaneous effect on the dependent variables with a calculated f value of 35.642 and a sig value of 0.000b.